Unraveling plant hormone signaling through the use of small molecules - Rigal, Adeline; Ma, Qian; Robert, Stéphanie (Frontiers in Plant Science, 2014)
Plants have acquired the capacity to grow continuously and adjust their morphology in response to endogenous and external signals, leading to a high architectural plasticity. The dynamic and differential distribution of phytohormones is an essential factor in these developmental changes. Phytohormone perception is a fast but complex process modulating specific developmental reprogramming. In recent years, chemical genomics or the use of small molecules to modulate target protein function has emerged as a powerful strategy to study complex biological processes in plants such as hormone signaling. Small molecules can be applied in a conditional, dose-dependent and reversible manner, with the advantage of circumventing the limitations of lethality and functional redundancy inherent to traditional mutant screens. High-throughput screening of diverse chemical libraries has led to the identification of bioactive molecules able to induce plant hormone-related phenotypes. Characterization of the cognate targets and pathways of those molecules has allowed the identification of novel regulatory components, providing new insights into the molecular mechanisms of plant hormone signaling. An extensive structure-activity relationship (SAR) analysis of the natural phytohormones, their designed synthetic analogs and newly identified bioactive molecules has led to the determination of the structural requirements essential for their bioactivity. In this review, we will summarize the so far identified small molecules and their structural variants targeting specific phytohormone signaling pathways. We will highlight how the SAR analyses have enabled better interrogation of the molecular mechanisms of phytohormone responses. Finally, we will discuss how labeled/tagged hormone analogs can be exploited, as compelling tools to better understand hormone signaling and transport mechanisms.